Trans-anethole Ameliorates Intestinal Injury Through Activation of Nrf2 Signaling Pathway in Subclinical Necrotic Enteritis-Induced Broilers - Yu, Caiyun; Tong, Yichun; Li, Qiming; Wang, Tian; Yang, Zaibin (Frontiers in Veterinary Science, 2022)
This study was conducted to investigate the alleviative effects of trans-anethole (TA) on intestinal oxidative stress through enhancing the activities of intestinal antioxidant enzymes and activating Nrf2 signaling pathway in subclinical necrotic enteritis (NE) infected broilers. A total of 192 1-d-old male Arbor Acres broilers were randomly allocated into three treatment groups: (1) control (CON); (2) subclinical NE challenge (NE); (3) NE challenge + 600 mg/kg TA (NE+TA600). Subclinical NE was induced by orally administration of live coccidiosis vaccine containing 2  104 oocysts at 10 days of age and 2 mL of Clostridium perfringens type A solution (3  108 CFU/mL) daily from days 14 to 19. The results showed that NE infection led to a severe decline (P < 0.05) in the final body weight (BW) and average daily gain (ADG), but an increase (P < 0.05) in feed/gain (F/G) of broilers at d 10-21 and d 1-21 compared with control group. TA administration improved (P < 0.05) the growth performance of NE birds. The intestinal villus height (VH) and villus height/crypt depth (VH/CD) were reduced (P < 0.05) by NE challenge as compared with those of control group, which was elevated by TA administration. Subclinical NE infection decreased (P < 0.05) serum activities of total superoxide dismutase (T-SOD), total antioxidant capacity (T-AOC), and jejunal and ileal glutathione peroxidase (GSH-PX) and T-SOD activity as well as T-AOC in the jejunum, while TA interventions positively elevated that (P < 0.05). Administration of TA protected the intestine against oxidative stress through up-regulation of intestinal nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway as compared with NE group (P < 0.05). In addition, dietary inclusion of TA elevated (P < 0.05) mRNA abundance of c-mesenchymal epithelial transition factor (c-Met), and jejunal epidermal growth factor receptor (EGFR) and transforming growth factor beta 1 (TGF-β1) in the jejunum and ileum of birds after subclinical NE challenge. In conclusion, 600 mg/kg of TA may be a promising tool to prevent and control subclinical NE by increasing intestinal antioxidant status in broilers.